Financial Literacy Levels of Fifth Grade Elementary School Students: An Ex Post Facto Quantitative Study - Maryam, Cucu; Fitriani, Andhin Dyas (International Conference on Elementary Education, 2025)
Financial literacy is a crucial 21st-century skill that should be developed from the elementary level to ensure students are able to manage economic resources wisely and responsibly. This study aims to analyze the financial literacy levels of elementary school students and to describe the tendencies of achievement for each phase C indicator of financial literacy. This quantitative study employed an ex post facto design, where researchers did not administer direct interventions, but examined the actual conditions of students' abilities based on assessment results. The instrument used was a summative financial literacy assessment covering nine principal indicators: understanding sources of income, socialresponsibility, budget planning, wise spending behavior, social expenditure allocation, loan responsibility, saving strategies, understanding inflation, and risk management. Data were analyzed quantitatively and descriptively to determine average scores and categorize financial literacy levels. The findings revealed that students’ financial literacy was generally in the moderate category, with the highest achievements in saving and social responsibility aspects, and the lowest in budget planning and risk management. These results indicate that while students’ conceptual understanding of the value and function of money is fairly developed, their daily financial decision-making skills still need to be improvedthrough more contextual and practical learning experiences.